6(3x-2)+4x=

Simple and best practice solution for 6(3x-2)+4x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3x-2)+4x= equation:


Simplifying
6(3x + -2) + 4x = 0

Reorder the terms:
6(-2 + 3x) + 4x = 0
(-2 * 6 + 3x * 6) + 4x = 0
(-12 + 18x) + 4x = 0

Combine like terms: 18x + 4x = 22x
-12 + 22x = 0

Solving
-12 + 22x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 22x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 22x = 0 + 12
22x = 0 + 12

Combine like terms: 0 + 12 = 12
22x = 12

Divide each side by '22'.
x = 0.5454545455

Simplifying
x = 0.5454545455

See similar equations:

| 5(y+6)+4= | | 2x+15=8x+8 | | 6x+16=21 | | 9m-3=-39+3m | | 6(x-1)+4=3(7x+1) | | 5(2t-3)+4t=30-t | | 4y-3=0+y | | 15x^2-34x+15= | | (-3)-(2)= | | 5p+3=4p+6 | | 20p-2p+4p=20p-6p | | -17x-20=14x+70 | | -4x-11x=-75 | | 2.5x+3=15-1.5x | | 2x+1=4x-15 | | 2x-7=x+6 | | 17-5x=9+3x | | 5x+9=2x+30 | | 2x^2-x+6=0 | | 4x^2-44x+96= | | 7x-1=4x-3 | | 4x+0.2=6.6 | | 5x+4-4x=12-29 | | n^2-n+4=0 | | 5x-11-4x=-5 | | p=4n-50 | | 6k^2+22k-8=0 | | (x+2)(x+5)=-2 | | 4w+12w-10=16w-10 | | (6+4)*2-7+9+18+(5+1*3)+5=688 | | 3(0.6+2n)-3.2=7.6 | | x(x-5)=x^2+3x+5 |

Equations solver categories